(untitled) (Psychology Travelogs, 2025)
The article deals with the causes, features, degrees of violation and psychological and pedagogical bases of sound perception correction in children with phonetic-phonemic underdevelopment (FFNM)-a complex speech disorder, which covers both defects of sound and underdevelopment of phonemic processes It requires an individual approach in corrective work, as each child may exhibit different combinations of speech difficulties. His timely detection and purposeful speech therapy is the key to successful speech and general development of the child. Systematic work by a speech therapist in close cooperation with parents ensures lasting positive results and creates conditions for the child’s successful socialization. The study was analyzed, which was attended by 15 preschoolers with phonetic phonemic underdevelopment, which showed that only 13% of children were fully formed phonemic perception. Most preschoolers have shown difficulties in repeating syllables with phonetically close sounds, differentiation of sounds and the correctness of the pronunciation of words, which indicates the lack of phonematic analysis and synthesis. After purposeful corrective work, preschoolers have significantly improved phonemic perception. This indicates the effectiveness of the techniques used and positive dynamics in the correction process. Early speech therapy is an important factor in successful speech development, as it ensures the formation of basic articulatory and phonetic skills in preschool age. The integration of classical techniques with modern technologies makes the educational process more efficient, flexible and interesting for the child. A comprehensive approach that takes into account the anamnestic data, individual features and purposeful work on the development of phonemic perception and sound, is the key to successful speech rehabilitation of preschool children.